2018
DOI: 10.18686/fm.v3i1.1055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crude Oil and Gold Prices on US Stock Market: Evidence for USA from ARDL Bounds Testing

Abstract: This paper explores the effects of changes in crude oil and gold prices on US Stock market movement. Daily data are used from the first business day of January, 1986 to December 30, 2016. Efficient unit root tests (DF-GLS and Ng-Perron) are applied to examine the time series property of the variables in terms of stationarity or non-stationarity. ARDL Bounds Testing is applied for co-integration. Both DF-GLS and Ng-Perron tests confirm non-stationarity of each variable and depict behavior of all the variables i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This relation does not found to exist after a crisis. Rahman and Mustafa (2018) observed that US stock market returns get affected negatively by changes in gold price. Al-Ameer et al (2018) analyzed that during the crisis and before the financial crisis 2008, there was a positive relation while after the crisis there was a strong negative relation in Germany.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…This relation does not found to exist after a crisis. Rahman and Mustafa (2018) observed that US stock market returns get affected negatively by changes in gold price. Al-Ameer et al (2018) analyzed that during the crisis and before the financial crisis 2008, there was a positive relation while after the crisis there was a strong negative relation in Germany.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Explored foreign direct investment has week symmetric influence on stock market. Phan et al (2018) Concluded that price uncertainty of crude oil has an inverse effect on corporate investment however, economies that are oil producers effected more as compared to oil consuming economies (Rahman and Mustafa, 2018). Moreover, significant change for gold prices but insignificant for Oil but in long run, relationship become change from negative to equilibrium point (Narayan and Narayan, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand stock market performance declines when there is a decline in exchange rates due to the increase in Oil Price (Sadorsky, 2001). Rahman and Mustafa (2018) suggested in a long run Oil prices has very insignificant effect on stock returns but Phan et al (2018) explore that Crude Oil price uncertainty has a negative significant effect on corporate investment. There are different scholars that have various perspectives with regards of association across macro-economic variables & stock market deviations, Sathyanarayana et al (2017) oil price shocks has a huge potential to transmit fluctuations in to stock return, but in case of oil producing countries, oil prices leads to high returns (Sadorsky, 2001) when development project set aside in a country hence macro-economic variables react differently.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation